الغزل والرثاء في الشعر الإماراتي دراسة ونقد - صالح أحمد الحميد
The topic of ghazal and lamentation is one of the most important topics of Arabic poetry, and the researcher has tried to combine them in one research, and this poses a great challenge, in addition to the problem of research in the ambiguity of some poems that I dealt with the purposes of Emirati poetry in general, in the researcher wants from this research, by collecting these two purposes, to focus on the poet's psychology in two completely different topics, so we see him as joyful and we see him as sad, and Here we study what resulted in both cases together, and that during a specific period of time starting from 1980 and ending in 2020, and therefore the researcher has put goals that must be achieved, such as accessing the contents of the love and elegiac poetry of Emirati poets, and standing on the nature of the Emirati poem in order to analyze its features and deduce its connotations. And to achieve the goals of this research, the research imposed itself sometimes by mixing the two approaches together in multiple places. The descriptive approach gave a statement of the types of pathos and flirtation and the extent to which the poet was influenced by them, while the analytical approach added an accurate description of what the Emirati poem carried from real and metaphorical expressions that include the eloquence and eloquence of the Arabs. The researcher expects to conclude from this research the importance of poetic purposes in Emirati literature, and the extent to which Emirati poets benefit from the experiences of their Arab surroundings or are influenced by international literature, and the extent of the importance of the love and elegance topics that the poet addressed in his poems, and the researcher sees clear contributions to this research in enlightening the way to complete the research process in the purposes of aerial poetry, such as praise, pride, and description, and entering more into the heart of the Emirati poem to reveal its literary aesthetics that deserves more research and investigation from academics.